Education-Intellektual Development of Youth in Education as a Pedagogical Problem - Karamova Mohinur Faxritdin qizi (International Journal on Integrated Education, 2022)
The article describes the creativeness of human consciousness, the emergence of intellekt issues of emotional intelligence, sex and intellect, intellectual insufficiency, intellekt issues of structure, the history of intellect, the relationship between the influence of biological and social factors, the goals of developing the intellektual capacity of young people.